2004
DOI: 10.1074/jbc.m311393200
|View full text |Cite
|
Sign up to set email alerts
|

The thrH Gene Product of Pseudomonas aeruginosa Is a Dual Activity Enzyme with a Novel Phosphoserine:Homoserine Phosphotransferase Activity

Abstract: The thrH gene product of Pseudomonas aeruginosa has been shown to complement both homoserine kinase (thrB gene product) and phosphoserine phosphatase (serB gene product) activities in vivo. Sequence comparison has revealed that ThrH is related to phosphoserine phosphatases (PSP, EC 3.1.3.3) and belongs to the L-2-haloacid dehalogenase-like protein superfamily. We have solved the crystal structures of ThrH in the apoform and in complex with a bound product phosphate. The structure confirms an overall fold simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…These kinetic constants were observed to be lower in comparison with those obtained for PSP enzymes characterized from either Hydrogenobacter thermophiles (K m of 1.6 mM), P. gingivalis (K m of 2.0 mM and 2.6 mM for phosphoserine peptides), or Pseudomonas aeruginosa (K m of 207 M) (26,36,37). We also observed that maximal SerB2 activity was observed in the initial 5 min and that inclusion of 0.01% Triton X-100 enhanced SerB2 activity by 15-20% (Fig.…”
mentioning
confidence: 80%
“…These kinetic constants were observed to be lower in comparison with those obtained for PSP enzymes characterized from either Hydrogenobacter thermophiles (K m of 1.6 mM), P. gingivalis (K m of 2.0 mM and 2.6 mM for phosphoserine peptides), or Pseudomonas aeruginosa (K m of 207 M) (26,36,37). We also observed that maximal SerB2 activity was observed in the initial 5 min and that inclusion of 0.01% Triton X-100 enhanced SerB2 activity by 15-20% (Fig.…”
mentioning
confidence: 80%
“…Specific roles in amino acid metabolism continued to be acquired in specific lineages of the bacterial tree; for example, the enolase phosphatase and the phosphoserine:homoserine phosphotransferase respectively in methionine and threonine metabolism. 139,140,150 The other major bacterial innovations were related to sugar metabolism and appear to have occurred somewhat later in bacterial evolution. These sugar metabolism enzymes arose throughout the HAD superfamily, though the cof assemblage appears to be the most dominant amongst them.…”
Section: Post-luca Evolution Of Had Superfamilymentioning
confidence: 99%
“…The related ThrH subfamily, which is restricted to the proteobacteria, participates in the threonine biosynthesis pathway by catalyzing a phosphoserine-homoserine phosphotransfer reaction, similar to the phosphate exchange reaction of SerB. 149,150 The PHOSPHO1 subfamily contains a peculiar C2 cap, which has three conserved cysteine residues, suggesting that it is stabilized by metal chelation. The vertebrate versions of this subfamily are believed to mobilize inorganic phosphate for skeletal matrix mineralization mineralization through their action on phosphocholine and phosphoethanolamine.…”
Section: Tetra-helical Caps: Psp-p5n-1 Assemblagementioning
confidence: 99%
“…These included GTP, CTP, UTP, PEP, and acetyl-and carbamoylphosphate. Phosphoserine and phosphothreonine were also tested, since they are known substrates of some phosphotransferase enzymes (21,22). The reaction mixture with PEP was subsequently analyzed by the two enzymecoupled assay, while the rest of the reaction mixtures were analyzed by ESI-MS for the presence of 4Ј-phosphopantothenate.…”
Section: Characterization Of a Third Isoform Of Pantothenate Kinase 2mentioning
confidence: 99%